THE POLICY OF DEVELOPING VIETNAM’S FUNDAMENTAL INDUSTRIES IN THE PERIOD OF CONTINUING TO PROMOTE INDUSTRIALIZATION AND MODERNIZATION OF THE COUNTRY - Nguyen Duc Hien; Bui Tien Dung (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
The article focuses on clarifying the Party’s leadership and direction in the development of fundamental industries through the periods from the 6th Congress to the 13th Congress of the Communist Party of Vietnam, at the same time, it points out the Party’s orientations and choices in developing fundamental industries in Vietnam’s socio-economic development strategy. This study also points out the State’s policies to support the development of fundamental industries over the past time and clarifies the current situation of fundamental industry development in the period 2011-2020. From there, recommend a number of policy solutions for fundamental industrial development in the period of continuing to promote industrialization and modernization of the country until 2030, with a vision to 2045. Code: 23042201